Hong Kong Med J 2019
DOI: 10.12809/hkmj198101
|View full text |Cite
|
Sign up to set email alerts
|

Natural clinical course of progressive supranuclear palsy in Chinese patients in Hong Kong

Abstract: Progressive supranuclear palsy (PSP) is a common type of atypical parkinsonism. To the best of our knowledge, there has been no study of its natural clinical course among Chinese patients. Methods: This retrospective study included 21 patients with PSP who had radiological evidence of midbrain atrophy (confirmed by magnetic resonance imaging) from the geriatrics clinics of Queen Mary Hospital and Tuen Mun Hospital. Clinical information was retrieved from clinical records, including age at onset, age at present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
(72 reference statements)
1
11
1
Order By: Relevance
“…1. The T1-weighted sagittal images were performed with echo time (TE) 9.09 ms, repetition time (TR) 2510.96 ms and voxel size 0.47*0.47*6mm 3 . The brainstem was divided into 3 sub-regions (midbrain, pons and medulla oblongata) on T1 midsagittal sections by drawing 2 cutting planes: the first line is between the superior pontine notch and inferior edge of the quadrigeminal plate (line1) and the second line is parallel to the first through the inferior pontine notch (line 2) ( Fig.…”
Section: Mri Acquisition and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…1. The T1-weighted sagittal images were performed with echo time (TE) 9.09 ms, repetition time (TR) 2510.96 ms and voxel size 0.47*0.47*6mm 3 . The brainstem was divided into 3 sub-regions (midbrain, pons and medulla oblongata) on T1 midsagittal sections by drawing 2 cutting planes: the first line is between the superior pontine notch and inferior edge of the quadrigeminal plate (line1) and the second line is parallel to the first through the inferior pontine notch (line 2) ( Fig.…”
Section: Mri Acquisition and Measurementmentioning
confidence: 99%
“…The prognosis of PSP is poor with increased risks of falls, dysphagia, aspiration pneumonia and pressure ulcer, leading to institutionalization and short survival time [3]. The mean survival is only 3 to 4 years after the diagnosis and 5.3 to 13.0 years at the onset of the disease [1].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported that pneumonia is more likely to occur together with dementia and other neurodegenerative diseases [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Attems et al [26], in an autopsy study of 308 hospitalized patients, found bronchopneumonia to be the cause of death in 45% and 28% of those with and without dementia, a significant difference, but neuropathologically-defined dementia subsets, including AD, VaD, DLB and PSP, were not statistically different in their pneumonia rates.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, predisposing factors to both bacterial pneumonia and pandemic viral lower respiratory infections are wintertime occurrence, older age, male sex, obesity, pre-existing cardiopulmonary conditions, and diabetes . Also implicated are age-related neurodegenerative diseases that cause parkinsonism and dementia [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Pneumonia-associated deaths have been estimated to be twice as high in subjects with dementia [43], and the apolipoprotein E4 allele, a genetic risk factor for Alzheimer's disease (AD), has been reported to be more common in subjects dying with severe Covid-19 disease [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Predisposing factors to both acute non-Covid-19 pneumonia and epidemic Covid-19 disease include wintertime occurrence, older age, and male sex, while obesity, pre-existing cardiopulmonary conditions, and diabetes are particularly associated with Covid-19 disease . Also implicated as risk factors for both are age-related neurodegenerative diseases that cause parkinsonism and dementia [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%